Optimization of Soursop (Annona muricata L.) Puree Concentration and Margarine on Quality of Muffins - Trifany, Lintang Ayu Nisa; Murtini, Erni Sofia (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2021)
AbstractReducing the fat used in muffin production is necessary to produce muffins with low-fat content without changing physical characteristics. This reduction can be achieved by adding ingredients with high fiber content, such as soursop. This study aims to obtain the optimum concentration of soursop puree and margarine to produce muffins with the best texture, pore size, moisture content, and lowest fat content. The method used in this study is the Response Surface Methodology with the Central Composite Design using two factors, the concentration of soursop puree and margarine. The optimum treatment results obtained were the concentration of 16.159% soursop puree and 27.391% margarine with a hardness response of 3.390 ± 0.144 N, a pore size of 0.529 ± 0.046 mm2, a fat content of 8.302 ± 0.328%, and moisture content of 33.269 ± 0.397%. The optimum muffins have fat content, fiber content, carbohydrate content, hardness, pore size, reddish, yellowish, and taste attributes that are significantly different from control muffins. Moisture content, ash content, protein content, volume expansion, baking loss, density, brightness, attributes of color, aroma, texture, pores, and overall were not significantly different from the control muffins.Keywords: margarine, muffin, optimization, soursop puree AbstrakPenggunaan lemak perlu dikurangi untuk menghasilkan muffin dengan kadar lemak rendah tanpa mengubah karakteristik fisik. Hal ini dapat dilakukan dengan cara penambahan bahan yang memiliki kadar serat tinggi, salah satunya buah sirsak. Penelitian ini bertujuan untuk mendapatkan konsentrasi penambahan puree buah sirsak dan margarin yang optimum agar dihasilkan muffin dengan tekstur, ukuran pori, dan kadar air terbaik serta kadar lemak terendah. Metode yang digunakan pada penelitian ini adalah Response Surface Methodology dengan rancangan Central Composite Design menggunakan dua faktor, yaitu konsentrasi puree buah sirsak dan margarin. Hasil perlakuan optimum yang diperoleh adalah konsentrasi puree buah sirsak 16,159% dan margarin 27,391% dengan respon kekerasan 3,390 ± 0,144 N, ukuran pori 0,529 ± 0,046 mm2, kadar lemak 8,302 ± 0,328%, dan kadar air 33,269 ± 0,397%. Muffin optimum memiliki kadar lemak, kadar serat, kadar karbohidrat, kekerasan, ukuran pori, kemerahan, kekuningan, dan atribut rasa yang berbeda signifikan dengan muffin kontrol. Kadar air, kadar abu, kadar protein, volume pengembangan, baking loss, densitas, kecerahan, atribut warna, aroma, tekstur, pori, dan keseluruhan tidak berbeda siginifikan dengan muffin kontrol.Kata kunci: margarin, muffin, optimasi, pure buah sirsak